Junior High School Education System in Islamic Boarding School Environment Area - Amin Basri; Melyani Sari Sitepu; Imam Rinaldi (Tarbiyah Departement collaboration with AMCA, 2022)
Islamic boarding schools in Indonesia have played an essential role as institutions to spread Islam and make changes in society for the better. It can be viewed from the education system to advance the quality of education in Islamic educational institutions such as Islamic boarding schools. This study aims to analyze the education system in the Galih Agung Private Junior High School Darularafah Raya Islamic Boarding School. This study uses qualitative research with a naturalistic qualitative approach. This study's data collection was done using observation, interview, and documentation techniques. Informants in this study were Ustadz and Ustadzah, who served at the Darularafah Raya Islamic Boarding School and several students and dyah. Data analysis techniques include data reduction, data presentation, and conclusion. The study results indicate that: 1) The education system at Galih Agung Private Junior High School consists of educational objectives, conditions of educators and students, curriculum, and facilities/ infrastructure. The supporting factors are as follows: Competent educators, wise caregivers, adequate facilities and infrastructure, a comfortable boarding school environment, and improving the quality of extracurricular activities, while the inhibiting factors are: Lack of awareness of students as a student, not accustomed to discipline and independence, and students feel lazy.